Mitogenic signaling pathways in the liver of growth hormone (GH)-overexpressing mice during the growth period - Martinez, Carolina Soledad (2016)
ABSTRACT: Growth hormone (GH) is a pleiotropic hormone that triggers STATs, ERK1/2 and Akt signaling, related to cell growth and proliferation. Transgenic mice overexpressing GH present increased body size, with a disproportionate liver enlargement due to hypertrophy and hyperplasia of the hepatocytes. We had described enhanced mitogenic signaling in liver of young adult transgenic mice. We now evaluate the activation of these signaling cascades during the growth period and relate them to the morphological alterations found. Signaling mediators, cell cycle regulators and transcription factors involved in cellular growth in the liver of GH-overexpressing growing mice were assessed by immunoblotting, RT-qPCR and immunohistochemistry. Hepatocyte enlargement can be seen as early as 2-weeks of age in GH-overexpressing animals, although it is more pronounced in young adults. Levels of cell cycle mediators PCNA and cyclin D1, and transcription factor c-Jun increase with age in transgenic mice with no changes in normal mice, whereas c-Myc levels are higher in 2-week-old transgenic animals and cyclin E levels decline with age for both genotypes. STAT3, Akt and GSK3 present higher activation in the adult transgenic mice than in the growing animals, while for c-Src and mTOR, phosphorylation in GH-overexpressing mice is higher than in control siblings at 4 and 9 weeks of age. No significant changes are observed for ERK1/2, neither by age or genotype. Thus, the majority of the mitogenic signaling pathways are gradually up-regulated in the liver of GH-transgenic mice, giving rise to the hepatic morphological changes these mice exhibit.